The Contribution of Emotion Regulation and Family Resilience Among Earthquake Survivors - Kristiyani, Veronica; Sitinjak, Charli; Srifianti, Srifianti (Bulletin of Counseling and Psychotherapy, 2025)
Natural disasters, such as earthquakes, often lead to severe crises and adversity in family life due to significant psychological, economic, and social pressures. This situation has been experienced by families who survived the earthquake in Cianjur Regency, Indonesia. These families face profound challenges and crises that have left them in vulnerable conditions. In such circumstances, the ability of families to adapt and recover, referred to as family resilience becomes crucial to ensuring the ongoing well-being of all family members. One important factor that can influence the development of family resilience is the ability of family members to manage and regulate their emotions adaptively in the face of post-disaster stress and uncertainty. Emotion regulation strategies have been shown to play a significant role in coping and adaptation processes within families during various crisis situations. Understanding how the implementation of specific emotion regulation strategies influences the development of family resilience is essential for providing appropriate support to help families overcome adversity and recover more effectively. However, research specifically examining the role of these emotion regulation strategies on family resilience among populations affected by natural disasters in Indonesia remains limited. This quantitative, non-experimental study investigates the role of two emotion regulation strategies cognitive reappraisal and expressive suppression in predicting family resilience among 100 survivors. Participants completed standardized measures of emotional regulation and family resilience. Data were analysed using multiple linear regression. Results showed that both cognitive reappraisal and expressive suppression significantly and independently predicted family resilience, with expressive suppression contributing more strongly to the model. These findings challenge the conventional view that suppression is universally maladaptive and suggest that, in high-stress contexts such as post-disaster recovery, suppression may serve as a short-term stabilizing mechanism. The study contributes to disaster psychology literature by highlighting the contextual function of emotion regulation strategies in fostering family adaptation. Implications include the need for culturally sensitive resilience interventions that integrate flexible emotion regulation training for affected families.